2006
DOI: 10.1074/jbc.m605203200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Aminopeptidase N (Proteobacteria Alanyl Aminopeptidase) from Escherichia coli and Conformational Change of Methionine 260 Involved in Substrate Recognition

Abstract: Aminopeptidase N from Escherichia coli is a broad specificity zinc exopeptidase belonging to aminopeptidase clan MA, family M1. The structures of the ligand-free form and the enzymebestatin complex were determined at 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
154
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(164 citation statements)
references
References 37 publications
(3 reference statements)
10
154
0
Order By: Relevance
“…We determined the X-ray crystal structure rPfA-M1 to 2.1 Å (Table S2). The structure confirmed that rPfA-M1 adopts the bacterial aminopeptidase N-fold (20,22,23), and comprises 26 ␣-helices and 7 ␤-sheets divided into 4 domains ( Fig. 2A).…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…We determined the X-ray crystal structure rPfA-M1 to 2.1 Å (Table S2). The structure confirmed that rPfA-M1 adopts the bacterial aminopeptidase N-fold (20,22,23), and comprises 26 ␣-helices and 7 ␤-sheets divided into 4 domains ( Fig. 2A).…”
Section: Resultssupporting
confidence: 55%
“…2A). The catalytic domain II (residues 392-649) adopts a thermolysin-like fold and contains the active site, incorporating the zinc-binding motif H 496 EYFHX 17 KE 519 and the well-conserved G 490 AMEN motif involved in substrate recognition (20,22,23 Inspection of the molecular surface of PfA-M1 reveals 2 openings to the active site cavity. The first opening (N-terminal channel) comprises a shallow 8-Å-long groove at the junction of domains I and IV (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crystal structures of ePepN, hErPepN [not published, deposited in protein data bank (PDB) with ID: 2XDT], F3, LTA 4 H, PepN from Neisseria meningitidis (NmPepN) and from Plasmodium falciparum (PfPepN) have been reported. [4][5][6][7][8][9][10] Within the M1 class peptidases, all enzymes have four domains except, LTA 4 H which has only three domains. First two domains (Domains I and II) share highest sequence and structural homology among all these structures including the LTA 4 H. The LTA 4 H has a unique C-terminal domain instead of Domains III and IV, probably required to perform the leukotriene hydrolase activity.…”
Section: Introductionmentioning
confidence: 99%